Prognostic and clinicopathological role of geriatric nutritional risk index in patients with diffuse large B-cell lymphoma: A meta-analysis - Cao, Dan; Zhang, Zongxin (Frontiers in Oncology, 2023)
Background: Previous studies have explored the relationship between the geriatric nutritional risk index (GNRI) and survival outcomes of diffuse large B-cell lymphoma (DLBCL) cases, but the results were inconsistent. Consequently, the present meta-analysis was conducted to investigate how GNRI affects DLBCL and its function in terms of prognosis. Methods: The Web of Science, PubMed, Embase, and Cochrane Library databases were thoroughly searched until January 18, 2023. We calculated combined hazard ratios (HRs) and 95% confidence intervals (CIs) to estimate the relationship between the GNRI and survival outcomes of patients with DLBCL. Results: This meta-analysis included seven articles involving 2,353 cases. A lower level of GNRI predicted dismal overall survival (HR=1.40, 95% CI=1.25–1.56, p<0.001) and inferior progression-free survival (HR=1.46, 95% CI=1.19-1.80, p<0.001) of DLBCL patients. Moreover, a low GNRI was significantly related to Eastern Cooperative Oncology Group Performance Status ≥2 (odds ratio [OR]=4.55, 95% CI=2.75–7.54, p<0.001), Ann Arbor stage III–IV (OR=2.91, 95% CI=2.38–3.57, p<0.001), B symptoms (OR=3.51, 95% CI=2.34–5.29, p<0.001), and extranodal disease (OR=2.90, 95% CI=2.32–3.63, p<0.001). Conclusion: A lower GNRI level predicted poorer short- and long-term prognosis in patients with DLBCL. A low GNRI was correlated with clinical factors of disease progression in DLBCL patients.